Concept of Ideal Marriage in Early Adults - Eka Sufartianinsih Jafar; Mustainah AR (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
This study aims to analyze how the concept of ideal marriage in early adulthood is. This study uses a qualitative approach with a survey research design by distributing questionnaires followed by 27 early adults. Their age was 19-25 years with a high school education background (26%) and university (74%). The research subjects are domiciled from several regions in Indonesia, namely Makassar, Gowa, Ketapang, Barru, Soppeng, Takalar, Pare-Pare, Malang, Tana Toraja, and West Kalimantan. The results showed that the concept of ideal marriage in early adulthood can be seen from: (1) age, namely in the age range of 23-26 years; (2) mental readiness 100%; (3) financial readiness at 96.3%; (4) moral readiness 96.3%; (5) communicating the number of children and parenting 96.3%; (6) understanding each other’s roles husband/wife 92.6%; and (7) religion by 92.6%. The implication of this research is to be a reference for individuals, especially those who are in the early adult phase in designing and determining the concept of an ideal marriage that will be lived. So that they can create a prosperous family and avoid divorce.